Pengaruh Kompetensi Dan Kemampuan Pemanfaatan Teknologi Terhadap Kinerja Pegawai Di Kantor Kecamatan Tamalanre Kota Makassar - Veronika Runyati Toja; Kamaruddin Kamaruddin; Ansar Mulkin Bas (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the influence of competency and ability to use technology on employee performance at the Tamalanrea District Office. The method used was multiple linear regression analysis and the sample taken was 25 employees. The results of this research have been tested for validity and reliability, and classical assumptions have also been tested in the form of normality tests, multicollinearity tests and heteroscedasticity tests. The results of this research show that the competency variable (X1) has a positive and insignificant effect on employee performance (Y), while the ability to use technology variable (X2) has a positive and significant effect on employee performance (Y). It can be concluded that together the competence and ability to use technology have a positive effect on employee performance at the Tamalanrea District Office, Makassar City, so it is hoped that each agency (Tamalanrea District Office Leadership) will continue to retain employees who have competence or broad knowledge of the field of work they do. .